(untitled) (Politeja, 2025)
The aim of the paper is to look into the processes of organizing censuses and to analyze them as a form of public policy reflecting but also shaping social relations. The paper acknowledges the challenges inherent in the running of censuses at the decentralized level and administered by different institutions. The content analysis of the census forms is used to track the changes introduced within the last decades and differences between censuses across the United Kingdom. The changes in the census questionnaires are presented as affected by external, sociodemographic factors, concurrent legislation, and political considerations.